La significación del "ingenium" en Juan Luis Vives - Hidalgo, Emilio (Revista Chilena de Humanidades, 2015)
In his article, Professor Hidalgo raises the problem of the efflcacy of theingenious in philosophy and in the humanistic tradition. With this regard, hisaim is to demonstrate the qualities of the ingenius method through an examination of the work of Vives. For thi s p urpose. it is cleerned necessa ry tounders tand the structure and the function of the in genius. which for theValencian thinker was one of the three elements of the higher soul. together with reason and judgement that are of such great significance in the fields oflenguage, rhetoric and dialectics. according to the Art of Teaching, as expounded by J.L. Vives.